Quick Identification of Specific Activity by Processing of Large-Size Videos Using Advanced Spotter - S.Hrushikesava Raju, Dr; M.Nagabhushana Rao, Dr; N.Sudheer, Dr; P.Kavitharani, Dr (International Journal of Engineering and Technology, 2018)
Now-a-days, the most organizations are using cameras at all places in order to monitor the activities going in their daily works 24/7 type. The purpose of recording all activities is to provide security and safeness to the property of their organization, as well as to find out the thefts happened or to identify any odd behavior of person about the complained situation. In this context, It takes more time to watch the long length video in predicting the right entity. There were other methods which require witness of some persons and time of the day. It is a manual approach to check the scene in the video recorded. It is unreliable. The alternative approach proposed is usage of advanced spotter in which cameras with sensors were attached in all places. The benefits of this proposed study is automatic fixing of spot in the recording of the videos when the objects behavior is predicted beyond the normal level. Hence, this automatic approach helps to the organizations where less time taken to find out the odd scenes which are tracked by the advanced spotter.Â Â